Rancher to the rescue - James, Arlene (James, Arlene. Three Brothers Ranch., 2019)
Coming to the aid of a woman in her broken-down car, Jake Smith finds the answer to his childcare problems. Kathryn Stepp needs a job, and the widower needs a nanny for his son. As they help each other, Jake is caught between attraction and his refusal to marry again. But sometimes a woman doesn<U+2019>t just fall for a hero<U+2014>she rescues him right back.